Mesalazine/hydroxypropyl-β-cyclodextrin/chitosan nanoparticles with sustained release and enhanced anti-inflammation activity. (15th October 2018) - Tang, Peixiao; Sun, Qiaomei; Zhao, Ludan; Pu, Hongyu; Yang, Hongqin; Zhang, Shuangshuang; Gan, Ruixue; Gan, Na; Li, Hui
Highlights: Phase solubility study confirmed the 1:1 stoichiometry of the HP-β-CD/MSZ complex. FT-IR, PXRD, 1 H-NMR, and 2D ROESY NMR analysis confirmed the complex formation. The HP-β-CD/MSZ/CS NPs exhibited an obvious sustained-release manner of MSZ. The HP-β-CD/MSZ/CS NPs exhibited better anti-inflammatory effects than free MSZ. Abstract: This study aimed to develop a novel sustained release system for mesalazine (MSZ) by preparing hydroxypropyl-β-cyclodextrin (HP-β-CD) inclusion complex loaded chitosan (CS) nanoparticles (NPs). The HP-β-CD/MSZ complex was prepared at 1:1 stoichiometry and characterized by using various analysis techniques. The HP-β-CD/MSZ/CS NPs prepared under the optimum condition had a spherical shape (90±17 nm diameter), a narrow size distribution, and a high loading efficiency. Compared with free MSZ, the HP-β-CD/MSZ/CS NPs exhibited an obvious sustained release of MSZ. The activity of the NPs against a cytokine-triggered inflammatory response was evaluated in cytokine-stimulated HT-29 cell lines by monitoring key inflammatory mediators. The results revealed that compared with free MSZ, the NPs more strongly inhibited the production of NO, PGE2, and IL-8, indicating the NPs possibly had better anti-inflammatory effects. Therefore, the established HP-β-CD/MSZ/CS NPs may be a promising delivery system of MSZ.